Attenuation of Spatial Memory in 5xFAD Mice by Halting Cholinesterases, Oxidative Stress and Neuroinflammation Using a Cyclopentanone Derivative - Rahim Ullah; Gowhar Ali; Nisar Ahmad; Muhammad Akram; Geeta Kumari; Muhammad Usman Amin; Muhammad Naveed Umar (MDPI AG, 2020)
Alzheimer's disease (AD) is an irreversible and chronic neurological disorder that gradually destroys memory and thinking skills. The research study was designed to investigate the underlying molecular signaling involved in the neuroprotective effects of cyclopentanone derivative i.e., 2-(hydroxyl-(3-nitrophenyl)methyl)cyclopentanone (3NCP) as a therapeutic agent for AD. In this study, In vivo studies were carried out on a well-known 5xFAD mice model using different behavioural test models such as open field, rotarod, Morris water maze (MWM), and Y-maze tests. Furthermore, in vitro cholinesterase inhibition activity assays were carried out. The frontal cortex (FC) and hippocampus (HC) homogenates were tested for the levels/activities of cholinesterases, glutathione (GSH), glutathione S-transferase (GST), and catalase. Furthermore, the hippocampal expression of inflammatory cytokines was observed via RT-PCR and western blot. The results of in vivo studies show an enhancement in the learning behavior. The 3NCP treatment reduced latency time in MWM and Y-maze tests, also increase spontaneous alternation indicate significant effect of 3NCP on memory. Furthermore, open field and rotarod studies revealed that 3NCP does not cause motor coordination deficit. The results of the in vitro studies revealed that the IC50 values of the 3NCP against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) were 16.17 and 20.51 µg/mL, respectively. This decline in AChE and BChE was further supported by ex vivo studies. Further, the 3NCP mitigates the GSH level, GST, and catalase activities in HC and FC. The mRNA and protein expression of inflammatory cytokines (IL-1β, IL-6, TNF-α) markedly declined in RT-PCR and western blotting. The results of the current study conclusively demonstrate that 3NCP reduces oxidative stress and mitigates neuroinflammation in 5xFAD mice, implying that 3NCP may be a potential therapeutic candidate for AD treatment in the future.